Pengaruh Kompetensi dan Budaya Kerja Terhadap Kinerja Karyawan Pada Kantor Notaris Moch. Farchan Ali Imron, S.H Kabupaten Grobogan - Anto Winarno; Pemilia Sulistyowati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
This research aims to determine the influence of competency and work culture on employee performance. The population in this study were all employees of the Moch Notary-PPAT Office. Farchan Ali Imron, S.H., Grobogan Regency. The strategy used in this research uses an associative research strategy using a quantitative descriptive approach because the research model developed is causal in nature. Researchers used questionnaires as a data collection tool. This research was measured using a Likert Scale with answers to each instrument item having a gradation from very positive to very negative.